(untitled) (Confluenţe Bibliologice, 2016)
The article reﬂectes the moments of civil servant and archivist activities fulﬁlled by Vasile Alecsandri. It is highlighted the reasons why the younger Vasile Alecsandri was promoted to the rank of Spathar (sword-bearer), then the great Spathar.